The Effect of Corporate Governance on ESG Investment Moderated by Gender Diversity on the Board of Directors - Chairiska Putri Meilinda Siregar; Fenny Marietza (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Thel aim olf this relselarch is tol invelstigatel thel impact olf colrpolratel golvelrnancel oln ElSG invelstmelnt, taking intol accolunt thel polssiblel moldelrating rollel olf gelndelr divelrsity in thel bolard olf direlctolrs olf Indolnelsian manufacturing elntelrprisels. In olrdelr tol fill an elmpirical gap in elarlielr relselarch, this study relfolcusels oln colrpolratel golvelrnancel (CG), which is linkeld tol ElSG invelsting throlugh thel applicatioln olf stelwardship thelolry. Thel usel olf gelndelr divelrsity oln thel bolard olf direlctolrs as a moldelratolr olf CG oln ElSG invelstmelnt is a nolvell approlach in this relselarch. Using thel Elvielws prolgram, multiplel linelar relgrelssioln with moldelrating variablels (MRA) is thel data analysis melthold useld in this study. This relselarch makels usel olf selcolndary data and a quantitativel meltholdollolgy. Manufacturing colmpaniels that welrel listeld beltweleln 2018 and 2022 oln thel Indolnelsia Stolck Elxchangel (IDX) colmprisel thel study's polpulatioln. Thirty colmpaniels with a toltal olf 150 olbselrvatiolns that satisfield thel samplel critelria madel up thel study's samplel. Thel study's findings sholw that gelndelr divelrsity oln thel bolard olf direlctolrs cannolt mitigatel thel impact olf colrpolratel golvelrnancel (CG) oln ElSG invelstmelnt in businelssels, and that CG has a colnsidelrablel impact oln ElSG invelstmelnt.